Enhancement Of Educational Technologies For The Development Of Competence In Future Economics Specialists - Nuralieva Maftuna Gulomovna (Genius Journals, 2025)
The article examines current issues regarding the enhancement of educational technologies for developing the professional competence of future economists. Modern approaches to fostering key competencies in economics students within the context of the digitalization of education are analyzed. The study aims to identify the most effective educational technologies that contribute to the development of analytical, communicative, and managerial skills in future economics specialists. The paper presents the results of an analysis regarding the application of interactive teaching methods, digital platforms, and a project-oriented approach in the educational process. Recommendations are proposed for the implementation of innovative educational technologies to improve the quality of training for economic specialists in accordance with the requirements of the modern labor market.
Keywords: educational technologies; professional competence; economic education; digitalization